2020
DOI: 10.1523/jneurosci.2618-19.2020
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an Amygdala–Thalamic Circuit That Acts as a Central Gain Mechanism in Taste Perceptions

Abstract: Peripheral sources of individual variation in taste intensity perception have been well described. The existence of a central source has been proposed but remains unexplored. Here we used functional magnetic resonance imaging in healthy human participants (20 women, 8 men) to evaluate the hypothesis that the amygdala exerts an inhibitory influence that affects the "gain" of the gustatory system during tasting. Consistent with the existence of a central gain mechanism (CGM), we found that central amygdala respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 92 publications
1
28
0
Order By: Relevance
“…A recent study by Veldhuizen, Small and colleagues ( Veldhuizen et al, 2020 ) showed that the CEA responses in humans were correlated with intensity ratings across multiple tastants and that these individual differences were also reflected in activation patterns in the thalamus. Their psychophysiological and dynamic causal modeling analyses suggested that inhibitory inputs from the amygdala to the thalamus act as a central gain mechanism that influences taste intensity perception.…”
Section: The Pvt Circuitries For Food Seeking and Consumptionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study by Veldhuizen, Small and colleagues ( Veldhuizen et al, 2020 ) showed that the CEA responses in humans were correlated with intensity ratings across multiple tastants and that these individual differences were also reflected in activation patterns in the thalamus. Their psychophysiological and dynamic causal modeling analyses suggested that inhibitory inputs from the amygdala to the thalamus act as a central gain mechanism that influences taste intensity perception.…”
Section: The Pvt Circuitries For Food Seeking and Consumptionmentioning
confidence: 99%
“…Thus, it is possible that the PVT contributed to the observed thalamic activity in that study, but was not specifically detected due to its size and limits of fMRI resolution. The PVT is interconnected with the CEA and insular cortex, and could be a missing link in the observed functional circuitry from the CEA to the insular cortex and to the ventral posterior medial thalamus, where the CEA impacted activity without direct connections ( Veldhuizen et al, 2020 ).…”
Section: The Pvt Circuitries For Food Seeking and Consumptionmentioning
confidence: 99%
“…This is an important issue because knowing whether central mechanisms play a significant role in interindividual variability in taste perception could help us understand not only individual differences in food preferences and diet, but also how gustatory circuit dysfunction may contribute to obesity. Veldhuizen et al (2020) hypothesized that inhibitory output from the central amygdala to gustatory brain regions act as a central gain mechanism that influences taste intensity perception. This idea is supported by three previous findings: (1) patients who had undergone surgical resection of the anterior medial temporal lobe, particularly those involving the amygdala, had increased taste sensitivity and stronger ratings of perceived taste (Small et al, 1997(Small et al, , 2001, which hinted at an inhibitory influence from the amygdala; (2) in directed attention tasks, amygdala circuits regulate gain by assigning greater weights to salient sensory sti-muli (Vuilleumier et al, 2004); and (3) Within the amygdala, the central nucleus is sensitive to changes in taste intensity perception, and this structure has reciprocal connectivity with all major gustatory regions (NST, VPM, IC; Small et al, 2003).…”
mentioning
confidence: 99%
“…This idea is supported by three previous findings: (1) patients who had undergone surgical resection of the anterior medial temporal lobe, particularly those involving the amygdala, had increased taste sensitivity and stronger ratings of perceived taste (Small et al, 1997(Small et al, , 2001, which hinted at an inhibitory influence from the amygdala; (2) in directed attention tasks, amygdala circuits regulate gain by assigning greater weights to salient sensory sti-muli (Vuilleumier et al, 2004); and (3) Within the amygdala, the central nucleus is sensitive to changes in taste intensity perception, and this structure has reciprocal connectivity with all major gustatory regions (NST, VPM, IC; Small et al, 2003). To test their hypothesis, Veldhuizen et al (2020) assessed blood oxygenation level-dependent (BOLD) responses to sweet, sour, salty, and bitter tastants in 28 healthy participants using psychophysiological measurements, regression, and dynamic causal modeling.…”
mentioning
confidence: 99%
See 1 more Smart Citation